1960
DOI: 10.1083/jcb.7.1.151
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Concentration of Solids in the Nucleolus, Nucleus, and Cytoplasm of the Developing Nerve Cell of the Chick

Abstract: Growing and differentiating nerve cells of the fifth cranial ganglion of the chick embryo were studied by several means. During the period of 70 hours to 11 days of incubation (Hamburger-Hamilton stages 19 to 37) average cell mass increased more than 4.5 times while cells changed from relatively undifferentiated neuroblasts to morphologically characteristic nerve cells with long processes. By making simplifying assumptions about thickness of nucleus and nucleolus, relative to cytoplasmic thickness, it was poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1960
1960
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The much denser nucleolus than other cell compartments is consistent with published measurements of cellular mass density by refractive index (Kim and Guck, 2020). The cellular mass density (the sum of protein and lipid density) ratio of these three compartments was around 1:0.85:1.05 (Supplementary Figure S2), close to the 1:0.8: 1.2 ratio found in chick nerve cells originally measured by interference microscopy (Merriam and Koch, 1960). Merriam et al found that the ratio was constant during chick embryo development.…”
Section: Protein Densities Are Maintained In Tight Ranges In Each Of ...supporting
confidence: 89%
“…The much denser nucleolus than other cell compartments is consistent with published measurements of cellular mass density by refractive index (Kim and Guck, 2020). The cellular mass density (the sum of protein and lipid density) ratio of these three compartments was around 1:0.85:1.05 (Supplementary Figure S2), close to the 1:0.8: 1.2 ratio found in chick nerve cells originally measured by interference microscopy (Merriam and Koch, 1960). Merriam et al found that the ratio was constant during chick embryo development.…”
Section: Protein Densities Are Maintained In Tight Ranges In Each Of ...supporting
confidence: 89%